KEHIDUPAN SUFISTIK PADA PONDOK PESANTREN BIBAá¸¤RI âASFARAá¸¤ SANANREJO, TUREN, MALANG - Musthofa, Musthofa (TEOLOGIA, 2015)
Abstract: The article will explore the sufiâs life at the Islamic boarding school (pesantren) Bibaá¸¥ri âAsfarah Sanarejo, Turen, Malang. The focus of study is the practies and how they practice to become a sufi, how their circumstance of mind when practicing, and how their circumstance of mind after practicing. The santri who never studying at the Pesantren can be divided three categories: al-FussÄq, al-Fusyl, and al-AbriyÄâ. The method used to a sufiâs life are mapped in two kinds of practices namely inward (bÄá¹iniya) and outward (lahiriya) practices. The inward practices include á¹£alawat (prayer for the Prophet Muhammad pbuh), istighÄá¹¡ah (mass prayer), asmÄâ al-á¸¥usnÄ (reciting name of God), YÄsÄ«n recital. The outward practices include spiritual traveling, cleaning the pesantren environment, installing paving and ornaments, making bricks, taking care of animal, becoming a sectary and treasures of the pesantren. Those inward practices are called riyÄá¸ah (the spiritual excercise). The soul circumstances (aá¸¥wÄl) while performing those practices could be described that they feel muá¸¥Äsabah (introspective), wuá¹£Å«l (pure), happy, excited, khauf (fearful), and rajÄâ (hopeful). Asbtrak: Artikel ini akan memaparkan kehidupan sufistik di Pondok Pesantren Bibaá¸¥ri âAsfarah Sanarejo, Turen, Malang. Fokus bahasan adalah amalan-amalan dan tata cara para santri dalam mengamalkan ajaran tasawuf sehingga mereka layak disebut sufi, keadaan jiwa selama dan setelah mereka mengamal ajaran tasawuf. Santri yang belum mondok dibagi dalam tiga kelompok: al-FussÄq, al-Fusyl, dan al-AbriyÄâ. Jalan yang santri tempuh menuju kehidupan sebagai sufi, antara lain, melalui pengamalan-pengamalan yang dipetakan menjadi dua jenis: pengamalan bersifat lahiriah dan batiniah. Yang termasuk pengamalan batiniah adalah pengamalan á¹£alawat, istighÄá¹¡ah, asmÄâ al-á¸¥usnÄ, membaca surat YÄsÄ«n; sedangkan pengamalan lahiriahnya adalah musafir, membersihkan lingkungan pondok, memasang paving dan ornament, mencetak bata, memelihara binatang, sekretaris, dan bendahara pondok. Pengamalan lahiriah ini disebut riyÄá¸ah. Keadaan-keadaan jiwa mereka (aá¸¥wÄl) mengamalkan ajaran tasawuf akan merasakan pengalaman-pengalaman spiritual (spiritual experience) seperti muá¸¥Äsabah, wuá¹£Å«l, senang, gembira, khauf, dan rajÄâ. Di lain pihak, para santri yang telah mengamalkan ajaran tasawuf tersebut akan mengalami perubahan yang baru seperti merasa senang, gembira, beriman, á¹£addiq, tenteram, wuá¹£Å«l, yakin, tawaá¸uâ, zuhud, dan ikhlas. Keywords: al-FussÄq, al-Fusyl, al-AbriyÄâ, tasawuf, dan sufi.